Integrin Alpha V in Urine: A Novel Noninvasive Marker for Prostate Cancer Detection - Zemskova, Marina Y.; Marinets, Maria V.; Sivkov, Andrey V.; Pavlova, Julia V.; Shibaev, Andrey N.; Sorokin, Konstantin S. (Frontiers in Oncology, 2021)
Prostate cancer (PCa) diagnosis based on patient urine analysis provides non-invasive and promising method as compared to biopsy and a prostate-specific antigen (PSA) test. This study was conceived to investigate whether Integrin alpha V (ITGAV) protein is present in urine and assess the urinary ITGAV diagnostic potential for PCa. Materials and Methods: Urinary ITGAV expression was determined by Western blot analysis and quantified by ELISA in urine from men with PCa (n = 47), benign prostate hyperplasia (n = 42) and age-matched controls (n = 22). Results: The level of ITGAV protein was significantly lower in PCa urine samples as compared to those in the control group (p < 0.00001). The decrease of ITGAV in urine was highly predictive of PCa with 91.5% sensitivity, 91.4% specificity, 0.93 area under the ROC curve, and its specificity was better than that of serum PSA. Conclusion: Urinary ITGAV provides a novel noninvasive biomarker with high specificity.